Survival of a Novel Subset of Midbrain Dopaminergic Neurons Projecting to the Lateral Septum Is Dependent on NeuroD Proteins - Khan, Shabana (J Neurosci, 2017)
Midbrain dopaminergic neurons are highly heterogeneous. They differ in their connectivity and firing patterns and, therefore, in their functional properties. The molecular underpinnings of this heterogeneity are largely unknown, and there is a paucity of markers that distinguish these functional subsets. In this paper, we report the identification and characterization of a novel subset of midbrain dopaminergic neurons located in the ventral tegmental area that expresses the basic helix-loop-helix transcription factor, Neurogenic Differentiation Factor-6 (NEUROD6). Retrograde fluorogold tracing experiments demonstrate that Neurod6(+) midbrain dopaminergic neurons neurons project to two distinct septal regions: the dorsal and intermediate region of the lateral septum. Loss-of-function studies in mice demonstrate that Neurod6 and the closely related family member Neurod1 are both specifically required for the survival of this lateral-septum projecting neuronal subset during development. Our findings underscore the complex organization of midbrain dopaminergic neurons and provide an entry point for future studies of the functions of the Neurod6(+) subset of midbrain dopaminergic neurons. SIGNIFICANCE STATEMENT Midbrain dopaminergic neurons regulate diverse brain functions, including voluntary movement and cognitive and emotive behaviors. These neurons are heterogeneous, and distinct subsets are thought to regulate different behaviors. However, we currently lack the means to identify and modify gene function in specific subsets of midbrain dopaminergic neurons. In this study, we identify the transcription factor NEUROD6 as a specific marker for a novel subset of midbrain dopaminergic neurons in the ventral midbrain that project to the lateral septum, and we reveal essential roles for Neurod1 and Neurod6 in the survival of these neurons during development. Our findings highlight the molecular and anatomical heterogeneity of midbrain dopaminergic neurons and contribute to a better understanding of this functionally complex group of neurons.